Onomastica piemontese 19: a cura di Alda Rossebastiano, Elena Papa, Daniela Cacia. (Studi Piemontesi, 2024)
The section illustrates and comments on the chronological and diatopic distribution of family names that are currently centred in Piedmont. In this papers, the surname forms associated with the types Lobbia and Gorgerino, borrowed from common vocabulary and speci- fically related to the domain of costumes, are examined. The etymology, medieval documentation, and an overview of their prevalence in both absolute and relative terms across different provinces are provided.